2017
DOI: 10.1111/j.1755-3768.2017.03623
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing microglia activation: a spatial statistics approach to maximize information extraction

Abstract: Summary Microglia play an important role in the pathology of CNS disorders, however, there remains significant uncertainty about the neuroprotective/degenerative role of these cells due to a lack of techniques to adequately assess their complex behaviour in response to injury. This talk briefly describes a novel technique for microglia analysis, combining improved immunohistological image analysis with spatial statistical techniques (Ripley‐K function and Dixon's χ2‐test). Using this approach, a comprehensive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 29 publications
1
26
0
Order By: Relevance
“…Compared to control mice, the average of soma size increased (56.85 vs. 68.32 μm 2 ) ( Figure 2D ). The result demonstrated the LPS exposure leads to activated microglia that features bigger soma size than ramified microglia called “resting” cells ( Kozlowski and Weimer, 2012 ; Davis et al, 2017 ). Taken together, these results demonstrate that LPS-induced neuroinflammation may activate microglia, leading to morphological alterations that suggest an activated state ( Liu and Hong, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…Compared to control mice, the average of soma size increased (56.85 vs. 68.32 μm 2 ) ( Figure 2D ). The result demonstrated the LPS exposure leads to activated microglia that features bigger soma size than ramified microglia called “resting” cells ( Kozlowski and Weimer, 2012 ; Davis et al, 2017 ). Taken together, these results demonstrate that LPS-induced neuroinflammation may activate microglia, leading to morphological alterations that suggest an activated state ( Liu and Hong, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…We found a general tendency of somewhat higher Iba1 immunoreactivity in R6/2 mice, which was significant in the hippocampus of 15 weeks old mice. There are several factors that may contribute to this difference, such as larger size of microglia, increased Iba1 expression, and a higher number of activated microglia ( Kozlowski and Weimer, 2012 ; Avignone et al, 2015 ; Davis et al, 2017 ). In fact, our panel of quantitative readouts generated during image analysis revealed that all these factors contribute to the differences in the percentage of immunoreactive area presented in Figure 6 .…”
Section: Discussionmentioning
confidence: 99%
“…For cell counting, eight non-overlapping images were taken at the peripheral or middle region of each retinal flatmounts at 200 × magnification, then cells were manually counted and averaged for each sample. Microglial soma size and roundness and nearest neighbor distance (NND) were quantified using methods and formulas developed by Davis et al [15].…”
Section: Immunostainingmentioning
confidence: 99%